Talent Management in the Public Sector - Tatjana Kozjek; Valentina Franca (Central European Public Administration Review)
Over the past decade, researchers and human-resource managers, particularly in larger private sector organisations, have shown an increased interest in talent management, while this issue has been overlooked in the public sector. The purpose of this paper is to present the literature review about talent management in the public sector and to show how the existing legislation allows the creation of a talent management system for Slovenian public sector organisations. The main methodological approach used was qualitative research with document analysis. The paper sought answers to three research questions: (How) are talented employees treated differently from other employees? What types of models or practices in the field of talent management are applied in European countries? What are the legal limitations in the field of civil servant talent management in Slovenia? The literature review shows that organisations that are aware of the importance and contribution to the ultimate organisational objectives treat talented employees differently from other employees in the organisation. Models or practices in the field of talent management vary widely among different European countries. The limitations in Slovenia are strict observance of the principle of equality and thus equal opportunities for inclusion in the system of talented civil servants with limited reward opportunities and, consequently, for the promotion of civil servants. In order to enable good practices in Slovenia, a change of the legal framework is necessary.